Exposure–response analysis reveals that clinically important toxicity difference can exist between bioequivalent carbamazepine tablets - Tothfalusi, Laszlo (Blackwell Science Inc, 2008)
AIMS: To assess whether, using the current regulatory criteria, therapeutically important differences can exist between bioequivalent carbamazepine (CBZ) tablets. A secondary goal was to demonstrate quantitatively the relationship between the risk of neurological adverse effects to orally ingested CBZ and the rate of absorption. METHODS: Results of a bioequivalence study by Olling et al. (Biopharm Drug Dispos 1999; 20: 19–28) were reanalysed. Following an exploratory data analysis step, a mixed-effect pharmacokinetic–pharmacodynamic (PK–PD) model was built to describe the dependence of adverse events on the CBZ concentration. RESULTS: Rapid development of tolerance was demonstrated for most neurological adverse effects, with a characteristic half-life of 02.29 h and an initial EC50 of 2.33 mg l(−1). The resulting tolerance PK–PD model was characterized further using the tools and terminology of sensitivity analysis. It was demonstrated that the maximum concentration (C(max)) exhibits poor PK and PD sensitivities, and that clinically significant differences can exist between formulations which otherwise comply with the bioequivalence requirements. In contrast, another PK metric, the partial AUC, was a much better marker of the early neurological adverse events observable during the absorption phase of the drug. CONCLUSIONS: In clinical and regulatory considerations, the development of acute tolerance for adverse effects of CBZ must be taken into account. Partial AUC reflects more sensitively the risk of adverse events than C(max). Instead of the current trend of tightening of the bioequivalence criteria for narrow therapeutic index drugs, the use of alternative, more sensitive PK metrics is proposed.